Diversity and classification of tall humid herb grasslands (Molinio‐Holoschoenion) in Western Mediterranean Europe. Issue 4 (21st August 2016) - García‐Madrid, Ana S.; Rodríguez‐Rojo, Maria Pilar; Cantó, Paloma; Molina, José A.
Abstract: Questions: What is the community diversity of tall, humid herb grasslands in Western Mediterranean Europe? What are the diagnostic species of the Molinio‐Holoschoenion alliance? What underlying ecological patterns influence their diversity? Location: Western Mediterranean Europe (France, Portugal and Spain). Methods: We compiled a vegetation plot database of Molinio‐Holoschoenion plant communities. The initial data set of 1056 plots was filtered according to physiognomic and floristic criteria, and geographically stratified. We used hierarchical agglomerative classification and semi‐supervised classification techniques based on the k‐means algorithm as a combination of methods to define vegetation types. A DCA analysis was performed to assess the main ecological drivers of diversity in the Molinio‐Holoschoenion community. Results: Seventeen vegetation types were defined, which can be classified in the following major vegetation groups: (1) tall humid grasslands on base‐poor and sandy soils; (2) Scirpoides holoschoenus grasslands on base‐rich soils; and (3) eastern Iberian and southwestern French Schoenus nigricans and/or Molinia caerulea grasslands. The water‐logging gradient was recognized as a major underlying pattern influencing the diversity and distribution of Molinio‐Holoschoenion, and at a second level, the soil factor. Conclusions: We suggest a revision of the concept of the Molinio‐Holoschoenion alliance to be considered for the interpretation of habitat type 6420 of the European Habitats Directive, which should include Mediterranean wet dune slacks and tall, humid inland grasslands. This vegetation type is largely distributed on the eastern Iberian Peninsula, where base‐rich soils are predominant and Scirpoides holoschoenus grasslands comprise the main floristic composition of the alliance. Abstract : We present a revised classification of the tall herb humid grasslands of Molinio‐Holoschoenion in western Mediterranean Europe, based on hierarchical agglomerative classification and semi‐supervised classification techniques. We propose seventeen vegetation types, and a list of diagnostic species. The water‐logging gradient and the soil chemistry were recognised as major underlying patterns influencing the diversity and distribution of Molinio‐Holoschoenion.